POLYPHENOLS AND ANTIOXIDANT ACTIVITY OF CASHEW NUTS FROM CONVENTIONAL AND ORGANIC CULTIVATION IN DIFFERENT STAGES OF PROCESSING - SOARES, DENISE JOSINO; DO CARMO, JÉSSICA SILVA; LIMA, JORGIANE DA SILVA SEVERINO; MAIA, GERALDO ARRAES; DE SOUZA, PAULO HENRIQUE MACHADO; DE FIGUEIREDO, RAIMUNDO WILANE (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
This research aimed to determine the total extractable polyphenols and the antioxidant activity of cashew nut obtained from conventional and organic cultivation. The study was performed with cashew nuts collected at four stages of processing: after shelling, before peeling, after peeling and during packaging. The antioxidant activity was measured by the methods with the radicals ABTS•+ and DPPH• and by the β-carotene/linoleic acid system. The nuts collected in the steps after shelling and before peeling presented higher antioxidant activity than those collected after peeling and during packaging. Little variation occurred in the content of total extractable polyphenols and antioxidant activity by ABTS•+ and DPPH• assays between the two cultivation methods studied.